Effective and Safe Use of Glucocorticosteroids for Rescue of Late ARDS - Paolo Diana; Dustin T. Money; Michael G. Gelvin; Nadia Lunardi (Case Reports in Critical Care)
We describe a case of severe refractory hypoxemia requiring prolonged extra corporeal membrane oxygenation (ECMO) support in a case of postpartum acute respiratory distress syndrome (ARDS). The clinical course was marked by persistently poor lung compliance and several complications of ECMO, that is, significant hemolysis, hemothorax, and intracranial bleeding. We report marked improvement of lung mechanics and respiratory function, leading to accelerated separation from ECMO, following rescue administration of low dose methylprednisolone 24 days after the onset of ARDS. Corticosteroid treatment was safe and well tolerated. In contrast with the conclusions of the 2006 ARDS Network trial, our report establishes a case in support of the use of low dose methylprednisolone as a safe and effective rescue treatment option in selected subsets of patients with nonresolving ARDS.